Wilms' tumor with intravascular extension: A review article - Suzanne McMahon; Robert Carachi (Wolters Kluwer Medknow Publications, 2014)
Intravascular extension of Wilms' tumor is a well-recognized phenomenon. Intravascular extension into the vena cava occurs in only 4-8% of patients with Wilms' tumors and intraatrial extension occurs in around 1-3% of patients. This review of the published literature in this cohort aims to summarize the findings of different case series to provide an optimum management plan. A literature search was performed and index papers were retrieved for review. The search included the following terms: Intracaval, intravascular, intraatrial and intracardiac extension of Wilms' tumor or nephroblastoma. The management of patients with intravascular tumor thrombus in Wilms' tumor is complex. A skilled multi-disciplinary team at a tertiary referral center with cardiothoracic surgery available should manage these patients. Multi-modal diagnostic and preoperative imaging are required to confirm and define the extent of the extension. Preoperative chemotherapy is advocated for all but exceptional circumstances and must be followed closely. Surgical resection should be planned according to the stage of intravascular extension with possible need for cardiopulmonary bypass and deep hypothermia with cardiac arrest if required. Surgical complications are more common in this group of patients, but outcome is comparable to those without intravascular extension, and is more closely correlated with the histological subtype then stage of intravascular extension. Operative imaging are required to confirm and define the extent of the extension.